2019
DOI: 10.1002/lary.28017
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the reflux symptom score

Abstract: Objectives/Hypothesis To develop and validate the Reflux Symptom Score (RSS), a self‐administered patient‐reported outcome questionnaire for patients with laryngopharyngeal reflux (LPR). Study Design Prospective controlled study. Methods A total of 113 patients with LPR were enrolled and treated with diet and 3 months of pantoprazole, alginate, and/or magaldrate depending on the LPR characteristics (acid, nonacid, or mixed). Eighty asymptomatic individuals completed the study. Patients and controls completed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
143
0
5

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 117 publications
(152 citation statements)
references
References 35 publications
(85 reference statements)
4
143
0
5
Order By: Relevance
“…Similarly, many digestive complaints associated with LPR are absent, although they predominate in LPR. [30][31][32] Lechien et al also identified RFS weakness in identifying clinical findings associated with LPR. This scale does not consider extra-laryngeal signs such as pharyngeal sticky mucus, pharyngeal wall erythema, and tongue tonsil hypertrophy, although many studies that reported that these signs may be associated with LPR.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, many digestive complaints associated with LPR are absent, although they predominate in LPR. [30][31][32] Lechien et al also identified RFS weakness in identifying clinical findings associated with LPR. This scale does not consider extra-laryngeal signs such as pharyngeal sticky mucus, pharyngeal wall erythema, and tongue tonsil hypertrophy, although many studies that reported that these signs may be associated with LPR.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline symptoms of patients have been assessed using the reflux symptom score (RSS) a few days before the MII‐pH. RSS is an easily administered, highly reproducible, reliable, and valid patient‐reported outcome questionnaire including respiratory; gastrointestinal; and ear, nose, and throat symptoms attributed to LPR . The U.S. version of RSS is described in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…In initial evaluation, non-laryngologists more frequently perform or refer for esophagoscopy, although less than 40% of LPR patients have GI findings such as hiatal hernia or esophagitis. 31,32 The majority of otolaryngologists believe that GI endoscopy is indicated for patients requiring long-term PPI therapy or those with refractory LPR. Only 14.2% of otolaryngologists recommend performing GI endoscopy in elderly LPR patients, while these patients are known to have a lower perception of esophageal irritation and a related higher risk of "silent" erosive esophageal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of specialty, the majority of otolaryngologists use once The selection of the symptoms including in the survey was based on the Reflux Symptom Score. 31 The numbers in the table consist of the percent of physicians who rate the symptom association: physicians had to choose from 1 (high-associated LPR symptom) to 5 (not associated with LPR). LPR = laryngopharyngeal reflux.…”
Section: Treatment Of Lpr Patientsmentioning
confidence: 99%